ANALYSIS OF THE ORTHOPEDIC PATHOLOGY STRUCTURE AND THE FREQUENCY OF REPEATED VISITS AFTER DENTAL PROSTHETICS WITH METAL-CERAMIC STRUCTURES - Radchuk, V.B.; Hasiuk, N.V.; Yeroshenko, G.A. (World of Medicine and Biology, 2019)
The article presents the materials of the retrospective monitoring of the patient’s card form 043/о to the results of the analysis of the structure of orthopedic pathology and the frequency of repeated visits of patients after prosthetics with metal-ceramic dental prostheses. The purpose of the study is to determine the relationship between the structure of orthopedic pathology and the frequency of repeated visits after prosthetics with metal-ceramic prostheses. Among the analyzed 986 dental charts in the structure of orthopedic pathology in I age group, defects of class III according to Kennedy prevailed, in the II age group – class II, in III age group – class I. The most frequent causes of retreatment were inflammatory changes in the gums in person’s І of the age group – 85,96 % and 73,77 % of patient’s ІІ. Patients of group III according to this criterion were 44,44 %. Loss of fixation or breakage of the prosthesis – 10,53 %, 19,67 % and 55,56 % respectively. Due to complicated caries, 3,51 % of patients in I age group and 6,56 % II. The results indicate errors at the stage of diagnosis and, accordingly, treatment, as well as violation of the protocol for the preparation of teeth for fixed orthopedic structures.
Keywords: metal-ceramic prostheses; breakage of the prosthesis; loss of fixation of the prosthesis; structure of orthopedic pathology